The Use Of Swear Words In Deadpool Movie: A Sociopragmatic Study - Khoirunnisa, Febrian Romadhonni, Agus Wijayanto, Ph.D (2017)
This research was descriptive qualitative study concerning with swear words. The data of this research were the utterance contain swear words in Deadpool movie script. The writers found five types of swear words in Deadpool movie, those are sex term, body part term, excretion term, death term, and animal term. The findings show that sex term was the dominant type because this type was mostly used by the characters in Deadpool movie. The writer also classify the category of swear words based on the context of the conversation and monologue found in Deadpool movie. The findings of this research show that there were seven categories of swear words used by the characters in Deadpool movie, such as intensifier category, exclamation of annoyance category, an insult category, exclamation of surprised category, rejection category, surprised question category, and the last is intensifier of unconcern category. The intention of using swear words by the characters that found in Deadpool movie showed that the characters in Deadpool movie used swear words not always to swear, but to express their other emotion and feeling in different situation.